On the competitive position of Eastern German manufacturing: Why is catching-up so slow? - Katja Gerling; Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Seven years after the transition from plan to market, it is hard to summon up much enthusiasm for the results of active restructuring of the eastern German economy. Although companies have made considerable efforts to reach the efficiency level of their western German counterparts, the gap is still large. In our paper, we provide a selective and interpretative account of the restructuring process in eastern German manufacturing. We start with modelling some economic relations which can be considered crucial in the restructuring process: ownership status and overall performance, sectoral and regional specialization, gross output and value added, investment and productivity, and wages and employment. In search of adjustment failures, we examine these relations by comparing the performance of eastern German with that of western German enterprises. Finally, we discuss the key policy question of how to overcome the difficulties. Without an about-face in wage policy, it will be difficult to shift the balance from wage convergence to efficiency convergence.
Keywords: P52; 330; Entwicklungskonvergenz; Systemtransformation; Reorganisation; Standortwettbewerb; Neue Bundesländer